Nature-inspired salt resistant bimodal porous solar evaporator for efficient and stable water desalination. Issue 5 (23rd April 2019) - He, Shuaiming; Chen, Chaoji; Kuang, Yudi; Mi, Ruiyu; Liu, Yang; Pei, Yong; Kong, Weiqing; Gan, Wentao; Xie, Hua; Hitz, Emily; Jia, Chao; Chen, Xi; et al.
Abstract : A bimodal porous evaporator is developed for efficient, stable, and salt-rejecting desalination of seawater and high-concentration brines. Abstract : The shortage of clean water is one of the predominant causes of human mortality, especially in remote rural areas. Currently, solar steam generation is being adopted as an efficient, sustainable, and low-cost means for water desalination to produce clean water. However, preventing salt accumulation during operation while maintaining long-term stability and a rapid evaporation rate is a critical challenge that needs to be urgently addressed to further facilitate the practical applications of solar desalination, especially for desalinating high-salinity brine. Here, we demonstrate that a bimodal porous structure ( e.g., balsa wood) can serve as an efficient and stable solar vapor generator for high-salinity brine desalination. Taking advantage of the inherent bimodal porous and interconnected microstructures of balsa wood, rapid capillary transport through the microchannels and efficient transport between the micro- and macrochannels through ray cells and pits in the bimodal evaporator can lead to quick replenishment of surface vaporized brine to ensure fast and continuous clean water vapor generation. The bimodal evaporator demonstrates a rapid evaporation rate of 6.4 kg m −2 h −1 under 6 suns irradiation and outstanding long-term stability for desalination of high salinity brine. The large vessel channels play a critical role in preventing salt from accumulating, as evidenced by controlled experiments with large vessels either blocked in the bimodal evaporator (balsa evaporator) or absent in a unimodal evaporator ( e.g., cedar wood) whose porous structure occurs naturally without large vessels. Both approaches demonstrate severe salt accumulation during solar desalination due to a lack of sufficient brine replenishment from the bulk solution beneath. With its unique bimodal porous and interconnected microstructure configuration obtained by a facile and scalable fabrication method, our bimodal porous structured evaporator device represents an efficient, stable, low-cost, and environmentally friendly solar vapor generator for high-salinity brine desalination.